THE EFFECTIVITY OF SEDIMENT TRAP IN THE CENTER LAND SALAK PADANGSIDIMPUAN AT SOUTH TAPANULI (Jurnal Online Pertanian Tropik, 2015)
West Angkola sub-districts and South Angkola are salak areas center of South Tapanuli that partly has undulating to hilly topographic with steep slopes that are potentially eroded. This study aims to determine the sediment trap and river on the land in the district Angkola West and East as well as the correlation between sediment discharge to the river flow and rainfall. The method used was survey methods and data analysis to quantify the Water Catchment Area for each Watershed by using software tools Arc Geographic Information System ( GIS ) 10.1. Sediment discharge calculated using the evaporation method. Regression data analysis using the software SPSS 19. Results showed the highest sediment discharge analysis on analysis in March in the District of East Angkola is 5.56 tons/day, while in April amounted to 9.2 tons/ha. Results of the analysis of sediment discharge peak in March in the District of West Angkola amounted to 0.74 tons /ha, while in April the sediment discharge is 1.1 ton/ha.